Zirconium-catalyzed intermolecular hydrophosphination using a chiral, air-stable primary phosphine. Issue 5 (27th October 2015) - Bange, Christine A.; Ghebreab, Michael B.; Ficks, Arne; Mucha, Neil T.; Higham, Lee; Waterman, Rory
Abstract : Catalytic hydrophosphination of alkenes using a chiral, air-stable primary phosphine, ( R )-MeO-MOPH2, proceeds under mild conditions with a zirconium catalyst to selectively furnish anti-Markovnikov, air-stable secondary phosphine or tertiary phosphine prodcuts with slight modification of the protocol. Abstract : Catalytic hydrophosphination of alkenes using a chiral, air-stable primary phosphine, ( R )-[2′-methoxy(1, 1′-binapthalen)-2-yl]phosphine, ( R )-MeO-MOPH2, proceeds under mild conditions with a zirconium catalyst, [κ 5 - N, N, N, N, C -(Me3 SiNCH2 CH2 )2 NCH2 CH2 NSiMe2 CH]Zr (1 ), to selectively furnish anti-Markovnikov, air-stable secondary phosphines or tertiary phosphines with slight modification of the protocol. An intermediate in the catalysis, [(N3 N)Zr( R )-MeO-MOPH] (4 ), was structurally characterized.